ANALYSIS OF TRANSLATION TECHNIQUES AND TRANSLATION QUALITY OF 2019 SOLO CALENDAR OF EVENT - Nunun Tri Widarwati; Arin Arianti; Ratih Wijayava (International Journal of English Linguistics, Literature, and Education (IJELLE), 2019)
This research aims at identifying translation techniques applied in translating theexpressions in 2019 Solo Calendar of Event and describing impact of translation techniques on the accuracy of translation of 2019 Solo Calendar of Event from Indonesian to English. It used qualitative research method. Data of the research were collected through content analysis and focus group discussion. They were then qualitatively analyzed. The research findings show that the translator employs nine translation techniques. Most of which are oriented to target language. The most dominant technique is established equivalent while the least dominant one is addition translation technique. In term of accuracy, the translation is categorized as high as indicated by the percentage of the accuracy which reaches 83.64%.